A Report of Primary Pyogenic Ventriculitis Caused by Streptococcus Constellatus Diagnosed by Metagenomic Next-Generation Sequencing - Zhang D; Deng M; Li F; Shen R (Infection and Drug Resistance)
Dongdong Zhang,1 Minnan Deng,1 Fenfen Li,2 Ruile Shen1 1Department of Neurology, The First Affiliated Hospital, and College of Clinical Medicine of Henan University of Science and Technology, Luoyang, 471003, People’s Republic of China; 2School of Pharmaceutical Sciences, Zhengzhou University, Zhengzhou, 450001, People’s Republic of ChinaCorrespondence: Ruile Shen; Fenfen Li, Email haikuopingyuyuehu@outlook.com; liff@zzu.edu.cnBackground: Primary ventriculitis is a rare but serious brain infection characterized by inflammation of the ependyma and purulence within the ventricular system. Due to the challenges in early diagnosis and the potential for suboptimal treatment, this condition carries a significant risk of complications such as recurrence, hydrocephalus, and death. Metagenomic next-generation sequencing (mNGS) enables the rapid and broad-spectrum identification of pathogens, facilitating timely and precise diagnosis.Case Report: This study presents the first reported case of primary ventriculitis caused by Streptococcus constellatus. An 81-year-old female patient with hydrocephalus and clinical signs of central nervous system infection was diagnosed with primary ventriculitis based on brain magnetic resonance imaging (MRI) and cerebrospinal fluid (CSF) analysis using mNGS. The patient underwent external ventricular drainage (EVD) and received a five-week course of ceftriaxone and linezolid. Following timely and targeted therapy, she demonstrated significant clinical improvement and was discharged without residual symptoms.Conclusion: Key insights from this case include: 1) mNGS is an invaluable tool for the early and accurate diagnosis of primary ventriculitis; 2) MRI is indispensable for identifying characteristic radiological features of the condition; 3) prompt initiation and completion of appropriate antibiotic regimens significantly improve clinical outcomes.Keywords: primary pyogenic ventriculitis, Streptococcus constellatus, metagenomic next-generation sequencing, mNGS